"I prefer to rise squared that go down round": metaphor and conceptual integration in religious meme - Bernardo, Sandra Pereira (2019)
Analyzes a religious imprint meme, created from the image traditionally conveyed in advertising Skol beer, based on theories of metaphor and conceptual blending (Lakoff & Johnson, 2002 [1980], FAUCONNIER; Turner, 2002). On a yellow background instead of the arrow with rounded red line pointing down around the name of the drink, is an arrow Red also forming angles of the base of a semi-open square, pointing up, around the word "heaven ". Below this image is the phrase "I prefer to go up square than to descend round". Among other possible assignments of meaning, an immediate relationship between the slogan and Skol evangelical dogmas about the straight posture and without vices to reach the sky was established. These two types of stored knowledge led to the opening of two mental spaces of input: the first compound of elements linked to the religious message and the second with elements related to the beer slogan. A generic space is open, bringing together elements common to both inputs and the conventional metaphorical conceptualization that BOM IS UP and BAD IS DOWN. The sense that the sky will only be achieved through a hard, square way, results from complex compressions between mental and intraespaços selectively projected onto the mixture space: ANALOGY, DISANALOGY, CAUSE-EFFECT, CHANGE, IDENTITY, SINGULARITY, INTENTIONALITY, MEMORY , LIFE'S HISTORY. It is a single-scope integration network in which the input on the advertisement serves as the source for the input of the meme message.